Dielectric properties of CuInP₂S₆ crystals under high pressure - Shusta, V.S.; Prits, I.P.; Guranich, P.P.; Gerzanich, E.I.; Slivka, A.G. (Condensed Matter Physics, 2007)
Dielectric properties of CuInP₂S₆ layered crystals in the range of ferrielectric phase transition are studied
under hydrostatic pressure. The pressure dependence of the phase transition temperature testifies to the
phase transition being of the order/disorder type. The (p, T) phase diagram of CuInP₂S₆ crystals has been
constructed. Дослiджено дiелектричнi властивостi шаруватих кристалiв CuInP₂S₆ в областi сегнетоелектричного фазового переходу при високих тисках. Барична поведiнка температури фазового переходу свiдчить про те, що цей фазовий перехiд вiдноситься до типу лад-безлад. Побудовано фазову (p, T) дiаграму кристалiв CuInP₂S₆.